2007
DOI: 10.1590/s0036-46652007000400001
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic and hemolytic activities of Candida dubliniensis strains

Abstract: SUMMARYCandida dubliniensis is an opportunistic yeast that has been recovered from several body sites in many populations; it is most often recovered from the oral cavities of human immunodeficiency virus-infected patients. Although extensive studies on epidemiology and phylogeny of C. dubliniensis have been performed, little is known about virulence factors such as exoenzymatic and hemolytic activities. In this study we compared proteinase, hyaluronidase, chondroitin sulphatase and hemolytic activities in 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 20 publications
(21 reference statements)
1
24
1
4
Order By: Relevance
“…C. dubliniensis possesses homologues of seven C. albicans secretory aspartyl proteinase genes (SAP) [29]. A prior study reported that proteinase activity of C. dubliniensis resulted in Pz range from 0.61 to 0.84 (mean = 0.75) [6], which is insignificantly low level of enzyme production when compared to the present result. In our study, proteinase production was observed at 66.66% and Pz ranged from 0.5-0.9 (mean=0.47) ( Table 1).…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…C. dubliniensis possesses homologues of seven C. albicans secretory aspartyl proteinase genes (SAP) [29]. A prior study reported that proteinase activity of C. dubliniensis resulted in Pz range from 0.61 to 0.84 (mean = 0.75) [6], which is insignificantly low level of enzyme production when compared to the present result. In our study, proteinase production was observed at 66.66% and Pz ranged from 0.5-0.9 (mean=0.47) ( Table 1).…”
Section: Discussioncontrasting
confidence: 76%
“…C. dubliniensis have been isolated from a wide range of geographical locations including Europe, North and South America, and Australia [22]. It recovered from several body sites in many populations, but it is most frequently recovered from the oral cavities of HIV-infected patients [6], and 15-30% has been reported from oral cavities of HIV-infected and AIDS patients [23]. Due to the use of inefficient sampling and identification methods or the sampling on the wrong anatomic sites, the prevalence of C. dubliniensis in normal healthy individuals has been underestimated probably [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymes involved in virulence, such as aspartyl proteinases, phospholipases, chondroitin sulfatase, and hyaluronidase, have been thoroughly studied. De Bernardis et al 24 and Linares et al 25 demonstrated that the level of aspartyl proteinase was signifi cantly higher in C. albicans than in C. dubliniensis, while no differences in phospholipase, chondroitin sulfatase, and hyaluronidase activities were observed [24][25][26] . In this study, we investigated the effect of fl uconazole and amphotericin B resistance on the SOD and catalase activities of C. albicans and C. dubliniensis.…”
Section: Discussionmentioning
confidence: 99%